2018
DOI: 10.1371/journal.pone.0190400
|View full text |Cite
|
Sign up to set email alerts
|

Early occurrence of inspiratory muscle weakness in Parkinson’s disease

Abstract: IntroductionIn Parkinson’s disease (PD), respiratory insufficiency (including functional and muscle disorders) can impact dysarthria and swallowing. Most studies of this topic have been performed retrospectively in populations of patients with advanced PD. The objective of the present study was to characterize lung function (under off-drug conditions) in early-stage PD patients at baseline and then again two years later.MethodsForty-one early-stage PD patients (mean ± SD age: 61.7 ± 7.7; mean ± SD disease dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 42 publications
2
67
0
4
Order By: Relevance
“…In one of the recent studies, by Baille et al. (), it was observed that PD patients exhibited inspiratory muscle weakness during the early stages of the disease. Thus, the mechanical changes observed in our study might also be correlated with stiffening of the lung and ribcage, which have also been observed in these previous studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In one of the recent studies, by Baille et al. (), it was observed that PD patients exhibited inspiratory muscle weakness during the early stages of the disease. Thus, the mechanical changes observed in our study might also be correlated with stiffening of the lung and ribcage, which have also been observed in these previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Parkinson's disease patients can experience an impairment in the tone, contractility and coordination of the thoracic musculature, affecting both respiratory mechanics and pulmonary functions (Baille et al., ; Owolabi et al., ; Reyes, Ziman, & Nosaka, ). Therefore, studies that evaluate the respiratory mechanics in a model of PD might lead to greater understanding of the effects of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there have been numerous studies of pulmonary function in PD, few have investigated the contributions of central and peripheral respiratory mechanisms using functional respiratory testing in patients with dyspnea. Table summarizes the key studies addressing pulmonary dysfunction in PD and shows the frequency of restrictive and obstructive patterns . Review of these studies shows a lack of consistent findings, which is likely due to the fact that they included diverse cohorts of patients at different stages of disease and used variable outcome measures.…”
Section: Studies Of Pulmonary Function In Pdmentioning
confidence: 99%